2021
DOI: 10.1080/14658011.2021.1902119
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of tape-based carbon fibre thermoplastic discontinuous composites for energy absorption

Abstract: Tape-based discontinuous composite is a relatively new type of composite material that offers improved mechanical properties for similar process-ability compared to Sheet Moulding Compound or Bulk Moulding Compound. This makes it potentially attractive for the automotive industry. In this paper, a thin-ply carbon fibre reinforced polypropylene-based discontinuous composite is studied. Mechanical tests are performed to obtain the tensile, compression and shear behaviour of the material. The energy absorption vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…8,37 In addition, these behaviors of composite structures have been confirmed in other studies as well. [16][17][18] The comparison of hysteresis loops in the different NR-foam formulations was depicted in Figure 10. It was noted that the area between the curve and the extension axis of a compressive force-stroke graph represents the energy absorbed or released by NR-foam samples.…”
Section: Energy Absorbedmentioning
confidence: 99%
See 1 more Smart Citation
“…8,37 In addition, these behaviors of composite structures have been confirmed in other studies as well. [16][17][18] The comparison of hysteresis loops in the different NR-foam formulations was depicted in Figure 10. It was noted that the area between the curve and the extension axis of a compressive force-stroke graph represents the energy absorbed or released by NR-foam samples.…”
Section: Energy Absorbedmentioning
confidence: 99%
“…Many studies have been performed to investigate the energy absorption properties of reinforced aluminum foam, 14 foam concrete, 15 and rigid assembled composite structures. [16][17][18] Furthermore, some studies [19][20] expressed an energy absorption property in terms of a hysteresis loss ratio to be easily compared to related works. However, it has been noted that the energy absorption properties of rubber foam for the laminated floor have received little attention in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis at 500 °C showed only a slight decrease in mass at the beginning, which was attributed to moisture removal. Francis et al [ 38 ] used a 450 °C temperature for resin burn‐off of carbon fiber composites. Therefore, it was concluded that a temperature of 400 °C should not damage the carbon fibers.…”
Section: Methodsmentioning
confidence: 99%
“…Although the burn-off method is more commonly used for the estimation of fiber volume fraction of glass-fiber composite materials, [35][36][37] it has also been used by Francis et al [38] for carbon fiber composites. McDonough et al also described a procedure to use the burn-off method for hybrid glass/carbon fiber composites.…”
Section: Fiber Weight and Volume Fractionsmentioning
confidence: 99%